Porphyrin-based Sensitizers in the Detection and Treatment of Cancer: Recent Progress - Vicente, M.G. (Current Medicinal Chemistry - Anti-Cancer Agents, 2001)
It has been known for some time that porphyrins and related compounds have the ability to selectively accumulate in tumor tissues, and to persist there for long periods of time. This property, along with the well-described photophysical and photosensitizing properties of porphyrin-type molecules, has led to their potential use as adjuvants and sensitizers in a variety of medical applications, such as in photodynamic therapy (PDT), boron neutron capture therapy (BNCT), radiation therapy (RT) and in magnetic resonance imaging (MRI). Both PDT and BNCT are binary cancer therapies that involve activation of tissue-localized sensitizers with either light (in PDT) or low-energy neutrons (in BNCT). In both of these therapeutic methodologies, local tumor control with minimal side effects relative to other forms of cancer treatment (surgery, radiotherapy, chemotherapy) can be achieved. Porphyrins constitute a major class of pharmacological agents currently under investigation. Photofrin, a porphyrin derivative, has been approved in the USA as a PDT drug by the U.S. Food and Drug Administration (FDA), and also in Japan, Canada and in eleven European countries. Recently, the FDA approved Visudyne, another porphyrin derivative for the PDT treatment of the wet-form of age-related macular degeneration. In addition to cancer treatment porphyrins are also under investigation for application in the treatment of a variety of other diseases.
Keywords: tumor targeting